Stability and Hopf Bifurcation in an HIV-1 Infection Model with Latently Infected Cells and Delayed Immune Response - Haibin Wang; Rui Xu (Discrete Dynamics in Nature and Society)
An HIV-1 infection model with latently infected cells and delayed immune response is investigated. By analyzing the corresponding characteristic equations, the local stability of each of feasible equilibria is established and the existence of Hopf bifurcations at the CTL-activated infection equilibrium is also studied. By means of suitable Lyapunov functionals and LaSalle’s invariance principle, it is proved that the infection-free equilibrium is globally asymptotically stable if the basic reproduction ratio for viral infection R0≤1; if the basic reproduction ratio for viral infection R0>1 and the basic reproduction ratio for CTL immune response R1≤1, the CTL-inactivated infection equilibrium is globally asymptotically stable. If the basic reproduction ratio for CTL immune response R1>1, the global stability of the CTL-activated infection equilibrium is also derived when the time delay τ=0. Numerical simulations are carried out to illustrate the main results.